« To Keep off the Company ». Étude d’une balustrade de lit royale du xviie siècle provenant d’Hampton Court - Sebastian Edwards (In Situ)
This article discusses the use and evolution of the royal bedchamber in seventeenth century England, through a unique case study of a surviving bed rail from Hampton Court Palace. This remarkable survival from the royal bedchamber has recently been discovered to date from before the English Commonwealth. It had previously been forgotten for many years before it was rediscovered in the nineteenth century, when it was first shown to the public as an altar rail from the royal chapel. More recently it has been associated with King Charles II: however, new technical and historical research has revealed that this rail was in fact made much earlier, during the reign of his father, Charles I, and before the period when English kings adopted the French ceremony of the lever and coucher. It now appears likely to have been made for his French queen, Henrietta Maria, who brought many novel fashions and possessions to England, including the use of a bed rail for her accouchements. Later alterations to the rail suggest it was soon adapted for Charles II, and perhaps his Queen, Catherine of Braganza, and then again used in the early eighteenth century by first Hanoverian King of Great Britain, George I. The final section of the article discusses how this unique object contrasts with the bedchamber furnishings of other English kings and queens in the later-seventeenth century, who developed their own distinctive form of bedchamber ceremony using a very different mode of bed rail. It is argued that this was in response to the new parliamentary monarchy in England, and contrasted to the focus on the royal body placed in the palaces of absolutist monarchs of France and many other European countries at this time.